Effect of hybridisation in laminated composites on the first ply failure behaviour: Experimental and numerical studies. (October 2019) - Biswas, Dhiraj; Ray, Chaitali
Highlights: Experimental first ply failure analysis of HFRP and GFRP laminates is conducted. Transverse shear stresses are computed using derivative of strain-displacement matrix. Warping effect is incorporated in refined higher order zigzag theory with C° continuity. Abstract: First ply failure analysis of hybrid laminated plate panels subjected to transversely applied static load is carried out and presented in this article. Hybrid laminates are fabricated in the laboratory as a combination of carbon and glass fabrics along with epoxy resin for this purpose. Strength and elastic properties of epoxy based laminates with carbon fibre (CFRP) and glass fibre (GFRP) are determined experimentally according to ASTM standard. Various multilayered hybrid laminates (HFRP) and GFRP laminates having all edges fixed boundary condition are tested under transverse static load. An improved eight noded quadratic isoparametric plate bending element based on refined higher order zigzag theory (HRZT) has been developed in the present study to evaluate the interlaminar stresses of multilayered composite laminates. The warping function has been considered in the displacement field to formulate a C° continuous plate bending element. The transverse shear stresses are computed in a simplified manner using the three dimensional differential equations of stress equilibrium. The first ply failure load is determined within linear and elastic range. The correctness and competence of the present finite element model is verified by comparing the solutions with relevant published data and also experimental outcome. The comparison between HFRP and GFRP laminates in terms of failure load has been made to identify the effectiveness of hybridisation. Graphical abstract: Image, graphical abstract